Client perspectives on choice of abortion method in England and Wales. Issue 4 (20th September 2021) - Blaylock, Rebecca; Makleff, Shelly; Whitehouse, Katherine C; Lohr, Patricia A
Abstract : Introduction: The National Institute for Health and Care Excellence, the Royal College of Obstetricians and Gynaecologists and the World Health Organization recommend that services provide a choice between medical and surgical methods of abortion. We analysed qualitative study data to examine patient perspectives on abortion method choice and barriers to meeting them. Methods: In-depth interviews with 24 clients who had an abortion at British Pregnancy Advisory Service clinics were carried out between December 2018 and July 2019 to examine perspectives of quality of abortion care. In this article we focus on client perspectives on choice of abortion method. We performed thematic analysis of data relating to choice of abortion method, refined the analysis, interpreted the findings, and organised the data into themes. Results: Participants' preferences for abortion method were shaped by prior experience of abortion, accessibility and privacy, perceptions of risk and experiences of abortion method, and information gathering and counselling. Participants' ability to obtain their preferred method was impacted by intersecting constraints such as appointment availability, service location and gestational age. Conclusions: Our findings show that many factors shape participants' preferences for abortion method. In response to the COVID-19 pandemic, some abortion services have constrained abortion method choices, with an emphasis on medical abortion and 'no-touch' care. Providers in the UK and beyond should aim to restore and expand more treatment options when the situation allows.